Sistem Informasi Manajemen Wisuda Menggunakan Metode Waterfall - Rizki, Uli; Mustofa, M Iqbal; Jakak, Pamuji M.; Khoiriyah, Septi (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The background of this research was several problems that were often encountered during the graduation period, such as inefficiencies in graduation registration due to having to go back and forth to campus, manually entering registration data, and long and crowded graduation lines. The goal is to overcome these obstacles with the help of today's website-based technology which is then called SIMUDA. Simuda was built using the PHP (Hypertext Preprocessor) programming language with the Laravel framework. The graduation information system research method uses the waterfall method, with the stages of needs analysis, modeling, and development (coding). The actors involved in using the system are students as graduation registrars of course and faculty administrative staff. In conclusion, this system has been able to overcome the problems underlying the development of this system. students are greatly helped because they can register for graduation without having to bother going back and forth to campus, it becomes easier for staff to see data recap of prospective graduates without having to check manually.